Now ICT malaria Pf/Pv® frente a microscopía (gota gruesa-extendido) para diagnóstico de malaria en Urabá (Colombia) (2010)
ABSTRACT: To date, there are only three reports from Colombia about the malaria diagnostic test Now ICT Malaria Pf / Pv ® (NowICT). The results from these studies showed major differences in sensitivity and specificity. Objective: To evaluate the diagnostic performance of NowICT compared to thick smear for the diagnosis of Plasmodium infection in matched blood samples from mothers (maternal peripheral blood), umbilical cord and placenta. Methods: We used a closed (blinded/masked) and parallel design for the evaluation of a diagnostic test. The sample size was calculated with statistical and epidemiological parameters; this consisted of 131 thick smears from maternal peripheral blood. Blood samples from placenta and umbilical cord were also studied (386 samples tested in total). Results: The sensitivity of Now ICT for detection of P. vivax was below 70% in any of the samples (maternal blood, placental blood or cord blood). The specificity was greater than 99%. Values for P. falciparum infection were not calculated since too few cases were detected. Conclusions: Now ICT Malaria Pf / Pv ® is not a useful diagnostic tool in Colombia since the sensitivity for the most frequent species in the country, P. vivax, is poor. This interpretation is consistent with the WHO’s general conclusions about the state of development of rapid diagnostic tests for malaria.